Prevalence of risk factors and estimation of 10-year risk for cardiovascular diseases among male adult population of Tamil Nadu India-an insight from the National Family Health Survey–5 - Midhun Sasikumar; Sam David Marconi; Aravind Dharmaraj; Kedar Mehta; Milan Das; Sonu Goel (Indian Heart Journal, 2023)
Objective: Cardiovascular diseases (CVD) are one of the most addressed preventable diseases of public health importance. However, the risk estimates and use of these risk scores for CVD prevention are the least explored areas. So, in this study, we explored the different categories of Framingham heart study (FHS) 10-year-CVD risk score and their associated factors among the adult male population in Tamil Nadu, India. Methods: We used the risk factor level data for male adults aged 18 years and above from the National Family Health Survey (NFHS-5) of Tamil Nadu state, India. Sociodemographic variables, behavioral factors, and physiological/biochemical factors were considered as the risk factor and were estimated using the world health organization (WHO) STEPS categories. FHS 10-year-CVD risk score was calculated using a body-mass index-based published Cox regression equation. Results: Out of 2289 adult males, only 1.12% of the participants had a 10-year CVD risk score greater than 30% and ∼4% of the total participants require statin treatment (FRS-CVD risk score ≥20). Educational status (aOR:14.21, 95 CI: 4.36–46.22- no formal schooling when compared to 10th and above standard), weekly fruit intake (aOR:0.51, 95 CI: 0.27–0.97 when compared to daily fruit intake) and abdominal obesity (aOR:2.43, 95 CI: 1.58–3.74) were found to be associated with higher FRS scores when adjusted for all other factors not involved in FRS calculation. Conclusion: Widespread use of this score needs to be encouraged in clinical practices and patients with a higher risk of CVD events should be counselled for lifestyle modifications and compliance with treatment for decreasing the burden due to CVDs.